A Framework for Sustainable Interoperability of Negotiation Processes - Cretan, A.; Coutinho, C.; Bratu, B.; Jardim-Goncalves, R. (Proceedings of the 14th IFAC Symposium on Information Control Problems in Manufacturing (INCOM’12), 2012)
The rise of new service-oriented technologies drives new ways to perform interoperability between companies, even in areas not directly connected to the enterprise core business. This paper proposes a framework to model and support sustainable interoperability of parallel and concurrent negotiations among organisations acting in the same industrial market, using a service-oriented platform. The underlying complexity is to model the dynamic environment where multi-attribute and multi-participant negotiations are racing over a set of heterogeneous resources. The metaphor Interaction Abstract Machines (IAMs) is used to model the parallelism and the non-deterministic aspects of the negotiation process, and a model-driven, cloud-based, service-oriented platform is proposed to manage a sustainable interoperability of the operating environment.